2014
DOI: 10.1007/s00455-014-9528-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Arabic Version of Dysphagia Handicap Index (DHI)

Abstract: The Dysphagia Handicap Index (DHI) is a 25-item self-administered questionnaire. It is a noninvasive tool for measuring the handicapping effect of dysphagia on the physical, functional, and emotional aspects of people's lives. The purposes of the present study were to develop an Arabic version of the DHI and to evaluate its validity, consistency, and reliability in the normal Arabic population with oropharyngeal dysphagia. This was a prospective study that was carried out at the Communication and Swallowing Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 15 publications
9
23
2
1
Order By: Relevance
“…P-DHI is a dysphagia-specific instrument and opposed to similar generic measures, it only limits the factors affecting the quality of life to dysphagia and not the other stressful events. In the present study, the mean P-DHI score was which is higher than what was reported by Silbergleit et al (9) and Farahat et al (14). Moreover, the highest P-DHI subscales score (worst QoL) was observed for the Physical subscale.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…P-DHI is a dysphagia-specific instrument and opposed to similar generic measures, it only limits the factors affecting the quality of life to dysphagia and not the other stressful events. In the present study, the mean P-DHI score was which is higher than what was reported by Silbergleit et al (9) and Farahat et al (14). Moreover, the highest P-DHI subscales score (worst QoL) was observed for the Physical subscale.…”
Section: Discussioncontrasting
confidence: 78%
“…It is a relatively new self-administered questionnaire that includes 25 items (9). The DHI has been translated into several languages such as Arabic (14), Persian (15), Japanese (16), and Hebrew (17). Factor structure analysis is a statistical method for investigating variable relationships for complex concepts such as socioeconomic status, quality of life, or psychological scales.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these tools were developed for studying certain disorders [3,27,28,29,30,31,32,33], while others have been criticized for being long, time-consuming, and for the difficulty in understanding individual items [19,34,35,36,37]. Serving the same purpose of developing a self-assessment tool of swallowing disorders, the Dysphagia Handicap Index was developed and translated into the Arabic language to provide valid and reliable patient-reported outcomes for dysphagia depending on the physical, functional, and emotional domains [38,39]. …”
Section: Discussionmentioning
confidence: 99%
“…Silbergleit et al [ 7 ] developed the DHI, which is a patient-administered 25-item questionnaire that measures the handicapping effect of dysphagia on the emotional, functional, and physical aspects of the patient's life. DHI was translated into Arabic language and was found to be a valid and reliable tool for patients with oropharyngeal dysphagia including patients with LPR [ 8 ].…”
Section: Introductionmentioning
confidence: 99%